1990
DOI: 10.1677/joe.0.1250021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of crude and highly purified bovine inhibin (Mr 32 000) on plasma concentrations of FSH and LH in chronically ovariectomized prepubertal heifers

Abstract: Chronically ovariectomized prepubertal heifers were used for a comparison of the effects of highly purified bovine inhibin (Mr 32,000) and steroid-free bovine follicular fluid (bFF) on the secretion of FSH and LH. In view of the limited availability of highly purified inhibin, an initial study was undertaken to establish the optimal method for administration of bFF inhibin activity. In comparison with the FSH response to a single large i.v. bolus injection of bFF (50 ml; 3250 mg protein), a far more effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…These results agree with the results obtained when either highly purified bovine or porcine inhibin was tested in rat pituitary cell culture (Robertson et al, 1985;Ling et al, 1987;Miyamoto et al, 1987) or injected in ovariectomized heifers (Ireland et al, 1983;Beard et al, 1990 (Nakamura et al, 1990; Kogawa et al, 1991;Shimonaka et al, 1991 Therefore, the purification of bovine inhibin with H256 as ligand may also copurify follistatin and activin,, and these bound proteins appear as a multiplicity of bands in the 25-35-kDa region. These results underline the potential problems of purifying inhibin by immunoaffinity chromatography from biological fluid.…”
Section: Dispersed Bovine Pituitary Cells In Culturesupporting
confidence: 86%
See 1 more Smart Citation
“…These results agree with the results obtained when either highly purified bovine or porcine inhibin was tested in rat pituitary cell culture (Robertson et al, 1985;Ling et al, 1987;Miyamoto et al, 1987) or injected in ovariectomized heifers (Ireland et al, 1983;Beard et al, 1990 (Nakamura et al, 1990; Kogawa et al, 1991;Shimonaka et al, 1991 Therefore, the purification of bovine inhibin with H256 as ligand may also copurify follistatin and activin,, and these bound proteins appear as a multiplicity of bands in the 25-35-kDa region. These results underline the potential problems of purifying inhibin by immunoaffinity chromatography from biological fluid.…”
Section: Dispersed Bovine Pituitary Cells In Culturesupporting
confidence: 86%
“…Inhibin has been identified as one of the proteins responsible for suppression of spontaneous FSH release (Ying, 1988;Ling et al, 1990;Knight, 1991). In cattle, it has been shown that injection of either BFF or purified inhibin reduces endogenous FSH concentration in the systemic circulation of intact (Miller et al, 1979;Quirk and Fortune, 1986;Lussier and Carruthers, 1989) hemiovariectomized Lussier et al, 1988) and ovariectomized cows (Ireland et al, 1983;Beard et al, 1990 the mixture at a ratio of 0.1 ml/ml of gel. The affinity gel column was equilibrated with 50 mM Tris-HCI, pH 7.5.…”
Section: Fsh I Lh I Inhibin I Follicular Fluid I Pituitary I Bovinementioning
confidence: 99%
“…Concentrations of total ir-α-inhibin were measured using the competitive radioimmunoassay reported by Knight et al (1989) and Beard et al (1990). Purified bovine 32 kDa inhibin A was used as the standard and the sensitivity of the assay was approximately 1 ng ml -1…”
Section: Hormone Determinationsmentioning
confidence: 99%
“…Additionally, it has been established that inhibin is responsible for the regulation of FSH secretion in cattle. Injection of steroid-free bovine follicular fluid [11] or highly purified bovine inhibin [12] has the ability to suppress FSH secretion in ovariectomized and cyclic heifers. Previous studies showed that the number of follicles 2 mm in diameter or larger was increased, by neutralization of endogenous inhibin u s i n g a c t i v e [ 1 3 -1 5 ] a n d p a s s i v e [ 1 6 -1 9 ] immunization, through a rise in the basal level of endogenous FSH.…”
mentioning
confidence: 99%